ANALISIS YURIDIS KEDUDUKAN HUKUM FATWA HALAL: STUDI PERBANDINGAN INDONESIA DAN THAILAND - Pratama, M. Angga; Shihab Bashari, Muhammad Alwi (LPPM Universitas Islam Ibrahimy Banyuwangi, 2026)
The increasinh demand for halal product in vaious countries, halal fatwa institutions play a very important role in issuing halal certificates. Given differences in certification systems between countries, it is very important to examine the legal basis and isntitutional structure of halal fatwa instituutions. This study is a comparative analysis between two countries with different systems, namely Indonesia and Thailand, highlighting how these two countries integrate Islamic legal principles into national regulations. This study uses a qualitative method with a comparative law approach to analyze legislation, institutional mandates, and administrative mechanisms that regulate the roles of the Indonesian Ulema Council (MUI), the Halal Product Guarantee Agency (BPJPH), and the Central Islamic Council of Thailand (CICOT). The findings show that Indonesia implements a dual authority model, in which MUI's halal fatwas obtain administrative power through BPJPH, thus forming a hybrid regulatory model. Thailand, on the other hand, uses a recognition model that centralizes fatwa and certification authority in CICOT, which is reinforced by scientific verification from the Halal Science Center. The research results confirm that although the two systems are structurally different, both contribute significantly to consumer protection, regulatory clarity, and the strengthening of the halal industry. This study emphasizes the importance of villages.